Combine the equations W = mg and `s = 1/(2*g*t^2)` to give an equation for W which does not involve g.

Expert Answers
justaguide eNotes educator| Certified Educator

From the equations W = mg and `s = 1/(2*g*t^2)` an expression for W has to be created that does not contain g.

`s = 1/(2*g*t^2)`

=> `2g*t^2 = 1/s`

=> `g = 1/(s*2*t^2)`

Substitute this for g in W = mg

=> `W = m/(s*2*t^2)`

The required expression is `W = m/(2*s*t^2)`

minnsy229 | Student

The answer to this should have actually been 2ms/t^2